Barriers to timely diagnosis and management of breast cancer in Africa: Implications for improved outcomes - Roland Muyisa; Emile Watumwa; Judith Malembe; Jacques Wahangire; Ghyslaine Kalivanda; Apollinaire Saa Sita; Soly Kamwira (Health Sciences Review)
Breast cancer (BC) is a significant health challenge in Africa, characterized by high incidence, morbidity, and mortality rates. This systematic review aims to identify factors delaying BC diagnosis and treatment, evaluate management outcomes, and highlight the contributing pathways.The study thoroughly searched electronic databases for articles on breast cancer in Africa, focusing on publications in English or French from the past decade. Independent reviewers screened the articles, extracting relevant data according to PRISMA guidelines.Barriers to early detection and management in Africa include poor symptom recognition, limited awareness, financial constraints, fear of diagnosis, and reliance on traditional medicine. Poor outcomes are often linked to advanced disease stages and larger tumor sizes, along with factors like the luminal B subtype and HIV status. Strategies to improve outcomes should focus on raising awareness, enhancing knowledge of hormonal tumor status, and implementing expedited referral pathways for women with concerning symptoms.Urgent measures for early detection and management are essential to address the breast cancer burden in Africa and improve patient outcomes.